End of empire 100 days in 1945 that changed Asia and the world - Chandler, David P. (David Porter) 1933-; Cribb, R. B.; Narangoa, Li (Copenhagen Nias Press, 2016)
Charts 100 days of dreams, drama and turmoil across eastern Asia at the end of World War II. Combines daily events with commentary, photographs, maps and personal accounts. Part of a radically new multi-layered, 'real-time' publication commemorating events 70 years after they happened and 'broadcast' day by day.
Includes bibliographical references (pages 314-320) and index.
Keywords: World War -- 1939-1945 -- Japan; Japan -- Foreign relations -- Asia; Asia -- Foreign relations -- Japan; Japan -- Foreign relations -- 1912-1945.